NORMALIZATION OF SERUM VITAMIN D IMPROVES SEMEN MOTILITY PARAMETERS IN PATIENTS WITH IDIOPATHIC MALE INFERTILITY - Alzoubi, A. (Acta Endocrinol (Buchar), 2017)
CONTEXT: Idiopathic male infertility is evident in half of infertile males. Vitamin D receptors are expressed throughout male reproductive tract, including spermatozoa, promoting motility. Epidemiological studies revealed the positive association between serum vitamin D and semen quality. However, there are no clinical studies examining the differential role of vitamin D in idiopathic male infertility. OBJECTIVES: 1) To investigate the association between vitamin D deficiency and idiopathic male infertility, and 2) To determine whether vitamin D deficient males would show restoration of semen quality parameters upon supplementation with vitamin D. DESIGN: This was a year-long case-control study from November 2015 to November 2016. A therapeutic intervention cohort for 2 months was also performed. SUBJECTS AND METHODS: 117 Jordanian males were enrolled. Following a clinical evaluation by a urologist, baseline serum vitamin D and semen fluid analyses were collected. Participants were stratified into 3 groups: controls (n=30), idiopathic infertility (n=67), and secondary infertility (n=20). Idiopathic infertility patients with low vitamin D (n= 45) were supplemented with oral vitamin D, 5000 IU, once daily for two months. Thereafter, serum vitamin D and semen fluid analyses were reassessed (n= 34; 11 patients were lost to follow up). RESULTS: Vitamin D was significantly lower in patients with idiopathic infertility than in both controls and men with secondary infertility. Significant improvement of progressive and total sperm motility was observed after vitamin D treatment. Vitamin D correlated significantly with semen quality in the study population. However, no correlation was found between vitamin D and any of the semen quality parameters in the idiopathic infertility group. CONCLUSIONS: Vitamin D supplementation improves sperm motility in idiopathic male infertility patients with low vitamin D. Larger and longer clinical trials are warranted to validate the use of vitamin D in these cases.